Assessing the Perceptions of Local Residents on the Positive and Negative Impacts of FIFA U-17 Women’s World Cup in Jordan 2016 - ALLAN, Mamoon (Journal of Environmental Management and Tourism; Vol 9 No 2 (2018): JEMT Volume IX Issue 2(26) Spring 2018, 2018)
Jordan is the first Middle Eastern and Arab country to host a FIFA U-17 Women’s World Cup. Thus, the main purpose of this study is to explore residents’ perceptions on impacts of this event and it further explores if there is a potential difference between males and females in their perceptions on the impacts of this event. The results of this study showed that ‘tourism resource development and urban revitalization’ was the main residents’ perception on the positive impacts of the event, whereas ‘negative economic perspective’ such as increased price of real estate was the main locals’ perception on the negative impacts. Furthermore, results indicated that variations in respondents’ perceptions commonly could be explained by their gender differences as male respondents indicated that they more highly perceived both positive and negative impacts of this event than local female respondents did.